Profile of Ophiocordyceps sinensis transcriptome and differentially expressed genes in three different mycelia, sclerotium and fruiting body developmental stages. Issue 10 (October 2018) - Zhong, Xin; Gu, Li; Wang, Haizhen; Lian, Danhong; Zheng, Yimei; Zhou, Sha; Zhou, Wei; Gu, Jinlei; Zhang, Guren; Liu, Xin
Abstract: Ophiocordyceps sinensis, a Chinese complementary and alternative medicine (CAM), is an entomopathogenic, fungus, parasitizing larvae of the moth genus Thitarodes . It has three stages of the life cycle, i.e., the anamorph mycelia prior to infection (Cm_Os), the mycelia sclerotium forming in the caterpillar (Te_Ca), and the fruiting bodies or stromata (Te_St). Characterization of the O . sinensis transcriptome among these stages could provide a better understanding of the underlying biology processes. Transcriptomics of the O . sinensis asexual mycelia and hyphae in deceased caterpillars and perithecial stroma was assessed by using Illumina HiSeq™ 2000 technology. A total of 14, 922 unigenes were identified and categorized into 46 sub-categories under three gene ontology categories ("biological process", "cellular component", and "molecular function"). Of these genes, 5520 were differentially expressed among the libraries of these three groups of samples ( P < 0.05), and 391 genes occurred in all three groups. Compared to the anamorph stage, there were 3049 differentially expressed genes (DEGs) in the teleomorph stage, but only 1023 DEGs occurred within the teleomorph groups (Te_St vs. Te_Ca). Collectively, this study provides a novel resource to further investigate O . sinensis and their three different development stages. Highlights: Transcriptome profiles of three developmental stages of O . sinensis were compared. Three thousand and forty-nine genes were differentially expressed between the teleomorph and anamorph stages. MAT genes were found not to be expressed in all three developmental stages.